The investigation of printing parameters effect on tensile characteristics for triply periodic minimal surface designs by Taguchi - Demir, Sermet; Temiz, Abdurrahim; Pehlivan, Fatih (Polymer engineering and science, 2024)
The advent of additive manufacturing also referred to as 3D printing, has brought about substantial changes in the industrial domain, as it possesses the capability to fabricate intricate items with enhanced cost‐efficiency and productivity. Fused Filament Fabrication (FFF) is a 3D printing process that has gained significant popularity due to its versatile capabilities and cost‐effectiveness. This paper investigates the impact of the printing parameters on the tensile characteristics of Triply Periodic Minimal Surface (TPMS) manufactured using FFF 3D printing. TPMS patterns have unique geometric properties and potential applications, making them an intriguing subject of study. The behavior of three different TPMS lattices with three printing parameters is investigated. Finding the best testing settings is done with the Taguchi method, and the data is analyzed with the Analysis of Variance (ANOVA) test. TPMS pattern was found to be the most effective parameter with 83.78%. While the highest strength was obtained in Schwarz diamond, the highest energy absorption was observed in the Gyroid structure. The contributions of printing parameters to tensile strength are line thickness, printing speed, and layer height, respectively. As line width and printing speed increase, both energy absorption and strength increase. Therefore, 0.40 mm line width and 60 mm/s printing speed give optimum values. When considered for energy absorption, the optimum value is 0.20 mm layer height, while when considered for strength, 0.10 mm layer height is the optimum value. The findings emphasize the importance of optimizing printing parameters for desired mechanical characteristics in 3D printed components and highlight the potential of TPMS structures in various applications. This research contributes to the growing knowledge in additive manufacturing and provides insights into optimizing FFF 3D printing for improved mechanical performance. Investigation of printing parameters affecting TPMS tensile specimens is conducted. Experimental design and ANOVA are employed to enhance mechanical performance. Gyroid, Primitive, and Diamond TPMS are manufactured with different printing parameters. TPMS structures are fabricated with FFF using PLA. Gyroid structure is highly suitable for energy absorption applications.